Hereditary Peripheral Neuropathies - Kuhlenbäumer, G.; Stögbauer, F.; Ringelstein, E. B.; Young, P. (Steinkopff : Imprint: Steinkopff, 2005)
"Hereditary Peripheral Neuropathies" deals with the Charcot-Marie-Tooth group of neuropathies and related primary hereditary neuropathies. The knowledge in this field has grown exponentially during the last ten years. The book is divided into two sections. The first section deals with the clinical presentation, electrophysiological features and differential diagnosis of these disorders as well as with the general biology of the peripheral nerve. The second section gives a detailed account of the known disease entities. The book will be interesting for both the clinician with a special interest in PNS diseases as well as for the researcher.